Artificial Intelligence-Based Talent Management and Its Impact on Employee Engagement and Organizational Resilience - Dicky Arpillo Siregar; Fatimah Pohan; Ramadani Ramadani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed human resource management, particularly in organizational talent management. This study examines the effect of AI-based talent management on employee engagement and its impact on organizational resilience. A quantitative approach was employed using a survey of employees from service organizations and knowledge-based industries in Indonesia. Data were analyzed using Structural Equation Modeling (SEM) to test direct and indirect relationships among variables. The findings indicate that AI-based Employee engagement is positively and significantly impacted by talent management, which in turn significantly influences organizational resilience. Additionally, AI-based talent management directly affects organizational resilience, both independently and through the mediating role of employee engagement. These results highlight the importance of AI-driven talent management in enhancing organizational adaptability and sustainability amid dynamic environmental changes.